UNDERSTANDING ETNOGRAPHY: MAPPING SOCIAL ECONOMIC CULTURAL BARRIERS OF JAMU GENDONG TRADERS IN SENGKED VILLAGE - Layung Paramesti Martha; Prasetyo Adinugroho (UNIVERSITAS PAKUAN, 2022)
Herbal or traditional medicine has become a mainstay sector in the cosmetic industry and blended herbs have a major contribution to the value of national exports and are capable of import substitution. However, the shift in culture and instant lifestyle has become a trend and has changed the character of traditional and modern society to shift from a culture of consuming traditional herbal medicine to being a consumer of factory/imported herbal medicine. This study aims to (1) Describe various social, cultural and economic practices of herbal medicine traders (jamu gendong traders) in Sengked Village which are built with verbal and nonverbal messages between jamu gendong traders and their consumers (2) Map out the economic, social and cultural barriers faced by jamu gendong traders. Sengked Village is an inland area of Bogor Regency where the characteristics of the local community are known to hold indigenous cultural traditions and local wisdom are the reasons that strengthen the research carried out in the village. The key informants in this study were herbal medicine traders in the category of early adulthood (26-35 years) to late elderly (56-65 years) (4). Meanwhile, the supporting informants from this study were community leaders, herbal consumers and the village officials of Sengked.